Use of biotic agents and abiotic compounds against damping off of cauliflower caused by Pythium aphanidermatum - S.K. SAIN, PRATIBHA SHARMA* and (Indian Phytopathology, 2005)
Damping off caused by Pythium aphanidermatum, is a major disease of vegetables including cauliflower throughout the world. The present study was attempted to understand the effects of abiotic compounds and biotic agents on the damping off disease control, plant vigour index, defense related enzyme activities and other biochemical parameters viz., phenylalanine ammonia lyase (PAL), peroxidase (PO) and polyphenol oxidase (PPO) activities, higher phenol and protein contents of pretreated challenged and untreated challenged cauliflower plants. Disease suppression (85-87%) was observed in Trichoderma harzianum, Aspergillus niger (Kalisena) and Bion treated plants as compared to chemical treatment. (60-84 %). Maximum plant vigour index (2127-2185) was observed in biological formulations in contrast to abiotic compounds (1461-1767). Enzyme activities (PAL, PO, PPO), total proteins and phenols were significantly higher in Bion, and biotic agent treated plants after third day of challenge inoculation as compared to other treatments. An extra specific protein band of Rf value 3.29 (molecular weight between 26-34 kDa) in SDS-PAGE was observed.